Phonetic Engine for Continuous Speech in Malayalam. Issue 5 (2nd September 2016) - Thennattil, Jubin James; Mary, Leena
ABSTRACT: This paper describes the work done towards implementing a phonetic engine (PE) for continuous speech in Malayalam. PE refers to a system that automatically converts input speech to a sequence of phonetic symbols. The PE described in this paper is built for continuous speech in Malayalam, which is speaker-, gender-, and domain-independent. For implementing the PE, a speech database is collected, which consists of speech in (1) read mode, (2) lecture mode, and (3) conversation mode. This data is transcribed using International Phonetic Alphabets. By analyzing the transcription, phonemes are mapped to 40 frequently occurring phonemes, which are then modelled using continuous Hidden Markov Model (HMM). The performance of this PE is evaluated using 1 hour 15 minutes of speech. A Graphical User Interface is developed for the PE to perform real-time recognition of speech.